2019
DOI: 10.3390/ijms20102563
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the Experimental Autoimmune Glaucoma Model from Rats to Mice—New Options to Study Glaucoma Disease

Abstract: Studies have suggested an involvement of the immune system in glaucoma. Hence, a rat experimental autoimmune glaucoma model (EAG) was developed to investigate the role of the immune response. Here, we transferred this model into mice. Either 0.8 mg/mL of the optic nerve antigen homogenate (ONA; ONA 0.8) or 1.0 mg/mL ONA (ONA 1.0) were injected in 129/Sv mice. Controls received sodium chloride. Before and 6 weeks after immunization, the intraocular pressure (IOP) was measured. At 6 weeks, retinal neurons, glia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…In a previous study, we already successfully transferred the EAG glaucoma model from rats to mice ( 49 ). Here, glaucomatous neurodegeneration was observed 6 weeks post ONA-immunization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we already successfully transferred the EAG glaucoma model from rats to mice ( 49 ). Here, glaucomatous neurodegeneration was observed 6 weeks post ONA-immunization.…”
Section: Discussionmentioning
confidence: 99%
“…WT (WT ONA) and KO (KO ONA) mice were immunized intraperitoneally with ONA (1 mg/ml) mixed with incomplete Freund's adjuvants (FA; 50 μl) and 1 μg pertussis toxin (PTx; both Sigma Aldrich, St. Louis, MO, USA) as described ( 49 ). To generate the ONA homogenate, fresh bovine eyes were obtained from a local slaughterhouse (Schlachthaus Wuppertal, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…In EAG mice that received a systemic immunization with optic nerve antigen homogenate (ONA), a significantly lower inhibitory post-synapses signal was visualized by anti-gephyrin in a later stage of degeneration, after six weeks. Gephyrin is encoded by the GPHN gene, and a significant downregulation of the Gphn mRNA was also found [ 59 ]. In our study, neither the systemically immunized animals nor the intraocular-injected ones showed any differences regarding the synapses labeled by gephyrin after 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…In a normal-tension glaucoma animal model, RGC death and optic nerve degeneration was observed in mice that were lacking the glutamate transporters GLAST or EAAC1, suggesting that glutamate transporters are necessary to prevent excitotoxicity [ 69 ]. Since VGluT1 is encoded by the Slc17a7 gene, a significantly lower level of its mRNA expression was found in ONA-immunized EAG mice after six weeks [ 59 ]. In the current study, we noted a tendency towards a higher VGluT1 signal in the systemically immunized S100B animals and a significant downregulation in rats receiving S100B intraocularly after 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…Tnc is also a key regulator of the 51 immune system and plays an important role during neuroinflammation and glial response 52 (Jakovcevski et characterized by an enhanced proliferation, migration, phagocytosis, and increased expression 58 levels of neuroinflammatory molecules (Langmann, 2007;Wolf et al, 2017). The neurotoxic M1-59 subtype has an amoeboid morphology and releases pro-inflammatory signaling molecules, like 60 tumor necrosis factor-alpha (TNF-α) and inducible nitric oxide synthase (iNOS) ( Louis, MO, USA) according to the previously described pilot study (Reinehr et al, 2019). FA 84 acted as an immunostimulatory and PTx was given to ensure the permeability of the blood retina 85 barrier.…”
Section: Introductionmentioning
confidence: 99%